2010
DOI: 10.2981/08-085
|View full text |Cite
|
Sign up to set email alerts
|

Can supplementary feeding be used to redistribute moose Alces alces?

Abstract: Foraging patterns, behaviour and the distribution of animals are affected by the availability and distribution of food in the landscape. Increasing numbers of ungulates may also be in conflict with agriculture, timber, infrastructure and conservation interests. Understanding foraging habits of ungulates and how these are affected by a change in forage availability or composition are, therefore, issues of major importance both from ecological and management perspectives. Supplementary feeding (i.e. artificial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 40 publications
0
44
0
1
Order By: Relevance
“…In a study regarding the use of supplementary feeding to redistribute moose in the Swedish forests [14] found that supplementary feeding affects moose movement, distribution and behaviour. [13,25] found that moose which use diversionary forage concentrated their space use around feeding stations with a decreasing probability of using areas away from feeding sites.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study regarding the use of supplementary feeding to redistribute moose in the Swedish forests [14] found that supplementary feeding affects moose movement, distribution and behaviour. [13,25] found that moose which use diversionary forage concentrated their space use around feeding stations with a decreasing probability of using areas away from feeding sites.…”
Section: Introductionmentioning
confidence: 99%
“…Game are also essential for forest ecosystem processes but their feeding activities (e.g., browsing) lead to costs in timber production [19,20]. Although in Sweden timber production and hunting for game have economic values [21,22] and some hunters and forest owners engage in improvement of game habitat to redistribute game activities in forests [14] to help reduce browsing damage in valuable forest stands e.g., young Scots pine trees, conflict of interests between foresters and hunters persist. Some forest owners perceive ungulates such as moose and deer as a problem due to economic losses they often incur from browsing damage [23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Placing bait stations or supplementary feeder sites is not expensive, particularly during harsh winters when ungulates will be attracted to even poor quality hay [102]. The tropical savannah version of this is using seasonal water holes during droughts and harsh dry seasons, when elephants and ungulates flock to any water they can find (Chamaillé-Jammes et al, 2007) [103].…”
Section: Impacts On Population and Ecosystemmentioning
confidence: 99%
“…Redistributing a population within a protected area therefore sometimes requires behavioural modification. Moose in Scandinavia have been redistributed by using supplementary feeding sites [102]. Elephants and ungulates in many African game parks have been dispersed or even attracted closer to tourist routes by using artificial water holes [103].…”
Section: Impacts On Population and Ecosystemmentioning
confidence: 99%